Tailoring Passivation Molecular Structures for Extremely Small Open-Circuit Voltage Loss in Perovskite Solar Cells - Yang, Shuang; Dai, Jun; Yu, Zhenhua; Shao, Yuchuan; Zhou, Yu; Xiao, Xun; Zeng, Xiao Cheng; Huang, Jinsong (Journal of the American Chemical Society, 2019)
Passivation of electronic defects at the surface and grain boundaries of perovskite materials has become one of the most important strategies to suppress charge recombination in both polycrystalline and single-crystalline perovskite solar cells. Although many passivation molecules have been reported, it remains very unclear regarding the passivation mechanisms of various functional groups. Here, we systematically engineer the structures of passivation molecular functional groups, including carboxyl, amine, isopropyl, phenethyl, and tert-butylphenethyl groups, and study their passivation capability to perovskites. It reveals the carboxyl and amine groups would heal charged defects via electrostatic interactions, and the neutral iodine related defects can be reduced by the aromatic structures. The judicious control of the interaction between perovskite and molecules can further realize grain boundary passivation, including those that are deep toward substrates. Understanding of the underlining mechanisms allows us to design a new passivation molecule, D-4- tert-butylphenylalanine, yielding high-performance p-i-structure solar cells with a stabilized efficiency of 21.4%. The open-circuit voltage ( V ) of a device with an optical bandgap of 1.57 eV for the perovskite layer reaches 1.23 V, corresponding to a record small V deficit of 0.34 V. Our findings provide a guidance for future design of new passivation molecules to realize multiple facets applications in perovskite electronics.